Protecting Female Workers Amidst the Controversy of Cheap Labor Market: A Comparative Advantage Analysis in Southeast Asia - Safitri, Dita Nur (UI Scholars Hub, 2025)
In Southeast Asia, the cheap labor market is frequently mentioned as one of the comparative advantages that drive growth in the economy. However, this market frequently employs harmful labour practices against female workers. This study investigates the intersection of gender, labour practices, and economic advantages in the region, concentrating on the obstacles and protective measures for female workers. The key objective of this study is to examine how female workers are protected in Southeast Asia's low-wage labour markets, as well as to assess the effectiveness of these safeguards in preventing exploitation and improving working conditions. This study uses a comparative analytical approach to assess different Southeast Asian countries' policies and practices regarding female workers in the labor market. It evaluates legal frameworks, enforcement procedures and the role of international organizations to advocate workers' rights. Data is collected using qualitative methods such as examining policy documents, and journal articles, and assessing labour market statistics. The data show a considerable gap in the protection of female workers throughout Southeast Asia. While some countries such as the Philippines, Malaysia, and Vietnam have adopted successful regulations and programmes, others have significant gaps in enforcement protection. The study emphasizes the need for stronger legal frameworks and enhanced implementation to guarantee that female workers advantage from the region's economic opportunities without being exploited or abused.